2022
DOI: 10.3390/jmse10081044
|View full text |Cite
|
Sign up to set email alerts
|

Gulf of Naples Advanced Model (GNAM): A Multiannual Comparison with Coastal HF Radar Data and Hydrological Measurements in a Coastal Tyrrhenian Basin

Abstract: High-resolution modelling systems have increasingly become an essential requirement to investigate ocean dynamics over a wide range of spatial and temporal scales, and to integrate the punctual ocean observations. When applied in coastal areas, they also have the potential to provide a detailed representation of transport and exchange processes at the sub-basin scale. This paper presents a validation exercise between the surface fields generated by the regional ocean modeling system (ROMS), developed for the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…On the other hand, the wind regime in the summer season is driven by breezes, with SW and NE winds alternating during the day, and with periods of stable atmospheric pressure due to the presence of the Azores anticyclone and, in the last few years, of the African anticyclone [34]. The circulation in the GoN, as shown by several modeling studies [25,33,35] and experimental investigations [36][37][38], is closely related to local winds.…”
Section: Hfr Networkmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the wind regime in the summer season is driven by breezes, with SW and NE winds alternating during the day, and with periods of stable atmospheric pressure due to the presence of the Azores anticyclone and, in the last few years, of the African anticyclone [34]. The circulation in the GoN, as shown by several modeling studies [25,33,35] and experimental investigations [36][37][38], is closely related to local winds.…”
Section: Hfr Networkmentioning
confidence: 95%
“…The GoN is a highly populated area in the Central Tyrrhenian Sea (Western Mediterranean Sea), characterized by the presence of several industrial, touristic and commercial activities [21,22]. The HF-GoN network-retrieved surface currents and wave parameters have been used in several studies to understand oceanographic and ecosystem processes such as surface transport [23,24], the validation of numerical models [25], assimilation in numerical models [26] and wave field and extreme event analysis [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…To track estimated connectivity among nearshore sites we first performed numerical simulations using a regional ocean modelling system (ROMS) developed for the Tyrrhenian Sea (2 km resolution); then, the results of this first simulation were used as initial and boundary conditions for a finer grid model called Gulf of Naples Advanced Model (GNAM), covering the Campania coast with a 500 m resolution to obtain high-resolution output. GNAM is a free-surface, terrain-following, primitive equations ocean model widely used for a broad range of applications [ 24 ] and recently validated for the Gulf of Naples (GoN) area using a multiannual comparison with coastal high-frequency radar data and hydrological measurements [ 25 ]. We then used the ROMS velocity fields to run a Lagrangian transport package of virtual passive particles released along coastal areas, following velocity fields and constrained to fixed release depths (1 m).…”
Section: Methodsmentioning
confidence: 99%
“…Kokoszka, Saviano, et al (2022) compared the model with in situ data and found that the monthly and interannual variabilities of the velocity components of the surface currents in the GoN were accurately reproduced (average annual correlation: 0.63).…”
Section: Methodsmentioning
confidence: 99%